A Modified Case Definition to Facilitate Essential Hospital Care During Ebola Outbreaks. (18th September 2018) - Huizenga, Erdi; van der Ende, Jacob; Zwinkels, Nick; Jimissa, Augustine; van der Ende-Bouwman, Carolien; van Rooijen, Ruurd; Kargbo, Brima; Agnandji, Selidji T; Hanscheid, Thomas; Goorhuis, Abraham; Grobusch, Martin P
Abstract: During the late phase of the large West-African Ebola virus disease (EVD) outbreak, the majority of patients were cared for in designated treatment centers. However, the preexisting healthcare infrastructure was already overwhelmed by the outbreak. This had a huge impact on other, non-EVD–related diseases, causing an unprecedented increase in morbidity and mortality, which most likely exceeded the toll due to EVD directly. Consequently, a crucial question is how to provide appropriate healthcare and safeguard functionality of a healthcare system that also serves patients not suspected or diagnosed to have EVD. Here, we report on the Lion Heart Medical Center's experience in Sierra Leone and note that a case definition of Ebola that is broader than those commonly applied may be better suited when it is necessary to identify atypically presenting, pauci-symptomatic cases. Abstract : Standard Ebola case definitions are appropriate for screening approaches in treatment centers. However, a broader case definition may be needed when it is necessary to identify atypically presenting, pauci-symptomatic cases.